2022
DOI: 10.1017/ice.2021.533
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to severe acute respiratory coronavirus virus 2 (SARS-CoV-2) and risk of infection among healthcare personnel

Abstract: Objective: To assess the rate and factors associated with healthcare personnel (HCP) testing positive for SARS-CoV-2 after an occupational exposure Design: Retrospective cohort study Setting: Academic medical center with sites in Minnesota, Wisconsin, Arizona, and Florida Subjects: HCP with a high or medium risk occupational exposure to a patient or other HCP with SARS-CoV-2 Methods: We reviewed the records of HCP with significant occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
3
9
0
Order By: Relevance
“…Ideally, research into risks of COVID-19 by occupation would be based on cases ascertained through systematic prospective follow-up of large cohorts of workers, with regular ascertainment of symptoms, clinical signs, and polymerase chain reaction (PCR) testing. As that has not been feasible, researchers have been forced to use proxy measures of incidence based on: PCR testing (4)(5)(6)(7)(8)(9)(10)(11), measurements of specific immunoglobulins against SARS-CoV-2 (12)(13)(14), symptoms and sickness absence (6), COVID-19 related hospital admission (7,15,16), or mortality from the disease (7,15,(17)(18)(19)(20)(21)(22). In most studies to date, with broad coverage of occupations, mortality from COVID-19 has been the outcome measure (7,15,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Ideally, research into risks of COVID-19 by occupation would be based on cases ascertained through systematic prospective follow-up of large cohorts of workers, with regular ascertainment of symptoms, clinical signs, and polymerase chain reaction (PCR) testing. As that has not been feasible, researchers have been forced to use proxy measures of incidence based on: PCR testing (4)(5)(6)(7)(8)(9)(10)(11), measurements of specific immunoglobulins against SARS-CoV-2 (12)(13)(14), symptoms and sickness absence (6), COVID-19 related hospital admission (7,15,16), or mortality from the disease (7,15,(17)(18)(19)(20)(21)(22). In most studies to date, with broad coverage of occupations, mortality from COVID-19 has been the outcome measure (7,15,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…At the bottom line, unresolved limitations inherently related to analysis of testing results call for cautious interpretation of risk for specific occupations which must be construed in the light of findings in earlier studies applying other methodological approaches2 3 10 33–36 and independent assessment of workplace risk factors, for instance, using job exposure matrices 6 37…”
Section: Discussionmentioning
confidence: 99%
“… 6 Also, the literature has shown that HCW-to-HCW exposure gives rise to a higher risk of SARS-CoV-2 infection than exposure to a patient, and this might contribute to the triggering of clusters. 7 …”
Section: Discussionmentioning
confidence: 99%